2003
DOI: 10.1167/iovs.02-0444
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Differential Microarray Analysis of Dexamethasone Induction Reveals Potential Mechanisms of Steroid Glaucoma

Abstract: The induction of TIGR/MYOC by DEX is HTM-specific, whereas its secretory and glycosylation characteristics are ubiquitous. The known functions of HTM-DEX-specific genes reveal the presence of protective and damaging mechanisms for regulation of IOP during DEX treatment. Besides TIGR/MYOC, other HTM-DEX-specific genes may be good candidates for linkage to glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 49 publications
11
108
0
Order By: Relevance
“…al., Invest Ophthalmol Vis Sci 46: e-abstract #1349, 2005. (Lo et al 2003;Zhao et al 2004;Vittal et al 2005;Keller et al 2007b) In addition, TGFβ has been shown to produce a shift in the proportion of TM versican mRNA splice variants increasing domains containing additional CS GAG attachment sites (Fig. 2).…”
Section: Alternative Splicing Of Ecm Componentsmentioning
confidence: 98%
See 3 more Smart Citations
“…al., Invest Ophthalmol Vis Sci 46: e-abstract #1349, 2005. (Lo et al 2003;Zhao et al 2004;Vittal et al 2005;Keller et al 2007b) In addition, TGFβ has been shown to produce a shift in the proportion of TM versican mRNA splice variants increasing domains containing additional CS GAG attachment sites (Fig. 2).…”
Section: Alternative Splicing Of Ecm Componentsmentioning
confidence: 98%
“…This includes a number of SLRPs, CSPGs, HSPGs, and other types of PGs (Table 1). (Murphy et al 1987;Tanihara et al 1995;Wirtz et al 1997;Knepper, P et al 1998;Friedman et al 2000;Friedman et al 2002;Ishibashi et al 2002;Knepper, P et al 2002;Borras 2003;Lo et al 2003;Filla et al 2004;Vittitow and Borras 2004;Zhao et al 2004;Chen et al 2005;Vittal et al 2005;Keller et al 2007b) Some specific core proteins have been localized to regions of the TM by immunohistochemistry using light or transmission electron microscopy. Perlecan was localized to the basement membranes of the TM beams and SC inner wall cells.…”
Section: Proteoglycansmentioning
confidence: 99%
See 2 more Smart Citations
“…A metabolic hypothesis has its clinical fundament in the clinically attested relationship between steroid hormones and drugs and glaucoma in a segment of the population [28]. Finally, and increasing in acceptance, is the genetic hypothesis [29,30], used in the search for the genes responsible for the disease and which, naturally, encompasses both hypertensive and normotensive cases, and defines glaucoma as a neuro-degenerative disease. We will begin with the last.…”
Section: Current Paradigmsmentioning
confidence: 99%